1989
DOI: 10.1101/gad.3.10.1534
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the HTLV-I Rex and HIV-1 Rev trans-regulatory proteins and their RNA response elements.

Abstract: The Rex proteins of types I and II human T-cell leukemia viruses (HTLV-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 65 publications
7
142
0
Order By: Relevance
“…All retroviruses must express both unspliced and spliced forms of their initial, genome-length RNA transcript during the viral replication cycle (reviewed by Pollard & Malim, 1998;+ Therefore, retroviral replication is dependent on the nuclear export of not only fully spliced viral mRNAs that are comparable to cellular mRNAs, but also of incompletely spliced viral mRNAs that are essentially analogous to cellular premRNAs+ However, eukaryotic cells have evolved mechanisms to block the access of such pre-mRNAs to cellular mRNA export factors until processing is complete+ Retroviruses have therefore had to evolve mechanisms for the nuclear export of their incompletely spliced transcripts that are at least in part distinct from the canonical cellular mRNA export pathway+ At least two different mechanisms utilized by retroviruses for the nuclear export of their unspliced transcripts have been identified+ Several simple retroviruses, including simian type D viruses and avian leukemia viruses, contain a structured RNA element, termed a constitutive transport element (CTE), that directly recruits a cellular RNA export factor (Bray et al+, 1994)+ In the case of the simian type D viruses, this cellular cofactor has been identified as Tap, a protein that is also believed to play a critical role in the final stages of cellular mRNA export (Grüter et al+, 1998;Kang & Cullen, 1999;Katahira et al+, 1999)+ Unlike simple retroviruses, several more complex retroviruses utilize a virally encoded adaptor protein, termed Rev in human immunodeficiency virus type 1 (HIV-1) and Rex in human T-cell leukemia virus type I (HTLV-I), to recruit a distinct cellular nuclear export factor, termed Crm1, to incompletely spliced viral transcripts (Fornerod et al+, 1997;Neville et al+, 1997;Stade et al+, 1997)+ Thus, Rev and Rex bind not only to a highly structured viral RNA element termed the Rev response element (RRE) in HIV-1 and the Rex response element (RxRE) in HTLV-I (Hanly et al+, 1989;Malim et al+, 1989), but also, via a short leucine-rich sequence, to the Crm1 nuclear export factor+ Although Crm1 is unrelated to Tap and does not play a direct role in cellular mRNA export, Crm1 and Tap share the ability to target viral RNAs to the cytoplasm by directly binding to components of the nuclear pore complex (Neville et al+, 1997;Katahira et al+, 1999)+ Recently, a third protein functionally analogous to HIV-1 Rev (H-Rev) and HTLV-I Rex has been identified in human endogenous retrovirus K (HERV-K) (Magin et al+, 1999;Yang et al+, 1999)+ The HERV-K are a family of endogenous viruses, estimated to be present at between 50 and 170 copies per haploid human genome, that first entered the human germ line ;30 million years ago (Medstrand & Mager, 1998;Tristem, 2000)+ The HERV-K are not closely related to any currently known exogenous ret...…”
Section: Introductionmentioning
confidence: 99%
“…All retroviruses must express both unspliced and spliced forms of their initial, genome-length RNA transcript during the viral replication cycle (reviewed by Pollard & Malim, 1998;+ Therefore, retroviral replication is dependent on the nuclear export of not only fully spliced viral mRNAs that are comparable to cellular mRNAs, but also of incompletely spliced viral mRNAs that are essentially analogous to cellular premRNAs+ However, eukaryotic cells have evolved mechanisms to block the access of such pre-mRNAs to cellular mRNA export factors until processing is complete+ Retroviruses have therefore had to evolve mechanisms for the nuclear export of their incompletely spliced transcripts that are at least in part distinct from the canonical cellular mRNA export pathway+ At least two different mechanisms utilized by retroviruses for the nuclear export of their unspliced transcripts have been identified+ Several simple retroviruses, including simian type D viruses and avian leukemia viruses, contain a structured RNA element, termed a constitutive transport element (CTE), that directly recruits a cellular RNA export factor (Bray et al+, 1994)+ In the case of the simian type D viruses, this cellular cofactor has been identified as Tap, a protein that is also believed to play a critical role in the final stages of cellular mRNA export (Grüter et al+, 1998;Kang & Cullen, 1999;Katahira et al+, 1999)+ Unlike simple retroviruses, several more complex retroviruses utilize a virally encoded adaptor protein, termed Rev in human immunodeficiency virus type 1 (HIV-1) and Rex in human T-cell leukemia virus type I (HTLV-I), to recruit a distinct cellular nuclear export factor, termed Crm1, to incompletely spliced viral transcripts (Fornerod et al+, 1997;Neville et al+, 1997;Stade et al+, 1997)+ Thus, Rev and Rex bind not only to a highly structured viral RNA element termed the Rev response element (RRE) in HIV-1 and the Rex response element (RxRE) in HTLV-I (Hanly et al+, 1989;Malim et al+, 1989), but also, via a short leucine-rich sequence, to the Crm1 nuclear export factor+ Although Crm1 is unrelated to Tap and does not play a direct role in cellular mRNA export, Crm1 and Tap share the ability to target viral RNAs to the cytoplasm by directly binding to components of the nuclear pore complex (Neville et al+, 1997;Katahira et al+, 1999)+ Recently, a third protein functionally analogous to HIV-1 Rev (H-Rev) and HTLV-I Rex has been identified in human endogenous retrovirus K (HERV-K) (Magin et al+, 1999;Yang et al+, 1999)+ The HERV-K are a family of endogenous viruses, estimated to be present at between 50 and 170 copies per haploid human genome, that first entered the human germ line ;30 million years ago (Medstrand & Mager, 1998;Tristem, 2000)+ The HERV-K are not closely related to any currently known exogenous ret...…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Rex activated RRE-1 mediated CAT expression 51-fold, whereas Rex in conjunction with Sam68 resulted in 4450-fold increase (Figure 1d). It has been shown that Rev is unable to reciprocate in transactivation of RxRE (Felber et al, 1989;Hanly et al, 1989), and we found that Sam68 failed to reconstitute the Rev function on RxRE-mediated transactivation (Figure 1e). These results indicate that Sam68 increases the activities of Rev-like proteins of all complex retroviruses examined.…”
Section: Sam68 Enhances Rex-and Erev-mediated Transactivationmentioning
confidence: 54%
“…They encode an RNA binding protein, Rev (HIV and EIAV) or Rex (HTLV), which binds to their RNA response elements, RRE or RxRE respectively (Hanly et al, 1989;Unge et al, 1991). In addition to the RRE/RxRE binding domains and a nuclear localization signal (NLS), both HIV-1 Rev and HTLV-1 Rex encode a leucine rich nuclear export signal (NES), which interacts with the nuclear export receptor CRM-1 (Fornerod et al, 1997;Neville et al, 1997; review by Mattaj and Englmeier, 1998).…”
mentioning
confidence: 99%
“…The effect of Rex on mRNA level is exerted in trans on the cis-acting Rex response e1ement (Rex RE), a highly stable RNA stem-loop structure in the U3/R region of the 3' L TR Hanly et al, 1989). Since the Rex RE stem structure is present in all viral mRNAs, the differential regu1ation of sp!iced versus unsp!iced mRNA by Rex also relies on other cis elements in the viral genome (Black et al, 1994a).…”
Section: Target Tissue (In Vitro and In Vivo)mentioning
confidence: 99%
“…NK-cell activity as weIl as CTL activity (see Section 4.2.3) may play an important role in !imiting the expansion of HTL V-I-infected T-cells at this stage, and progression to A TLL requires a number of additional events. Whereas HTL V -1 producer T -cell lines express high levels of the adhesion molecules LF A -1, LF A -3 and ICAM -1, A TLL-deri ved cell 1ines show reduced expression of these surface markers (Fukudome et al, 1992) (Gazzolo & Duc Dodon, 1987;Duc Dodon et al, 1989), but the interpretation of this phenomenon remains controversiaI. Recombinant HTL V -1 envelope protein, expressed in a vaccinia virus vector (Cassé et al, 1994) does not induce T-cell proliferation.…”
Section: Iarc Monographs Volume 67mentioning
confidence: 99%